Bioelectromagnetic Health and Healing - Valone, Thomas; Panting, Jacqueline (European Journal of Applied Sciences, 2024)
The following information is provided for educational purposes only. It is not to be construed as constituting medical advice, nor do the devices described have FDA approval though some qualify for the FDA grandfather clause which is an exemption. This article is not intended for diagnosis or treatment of disease. Persons should seek medical counsel before any investigation of these experimental devices.